2021
DOI: 10.31332/ijtk.v2i1.14
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Perceptions of The Benefits of Project-Based Learning in Translation Class

Abstract: This study aims to describe students’ perceptions of the benefits of project-based learning in translation class. The project focuses on the students’ perceptions and the benefits of translation project. The research method uses a qualitative approach with descriptive data analysis technique. The participants of this study consist of 25 university students. The qualitative data were analyzed by questionnaire and students’ reflection adopted from Siregar (2018). The results of the research revealed that the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The findings revealed that the students saw PBL positively. This is in line with the findings reported by Moghaddas & Khoshsaligheh (2019) and Astuti et al (2021). Further,…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings revealed that the students saw PBL positively. This is in line with the findings reported by Moghaddas & Khoshsaligheh (2019) and Astuti et al (2021). Further,…”
Section: Discussionsupporting
confidence: 93%
“…This implies that the project facilitated the development of students' understanding that translation involves more than simply producing the target text from a given source text. It also encompasses the acquisition and application of effective interpersonal skills to successfully complete translation tasks as well as adherence to professional codes of conduct as part of a professional community Astuti et al (2021). conducted a study to describe students' perceptions on the benefits of PBL in translation class.…”
mentioning
confidence: 99%
“…Language learning is a complex thinking process of investigating, exploring, and gaining. It requires a high rate of thinking and formulating so that it can lead to a good language's translation, comprehension, or production (Astuti et al, 2021). Engaging in project-based learning impacts students' learning level and promotes comprehensive understanding through a studentcentred approach.…”
Section: Project-based Learningmentioning
confidence: 99%
“…In this century, technology and information are very important (Astuti et al, 2021) and cannot be separated from daily life. This can be ascertained by the habit of a person starting from waking up until he will fall asleep again they cannot be separated from his cell phone.…”
Section: Introductionmentioning
confidence: 99%